Republican Gomorrah : inside the movement that shattered the party - Blumenthal, Max, 1977- (Nation Books, 2009)
An intimate, investigative portrait of how the purveyors of the politics of personal crisis and redemption brought down the GOP--and why they're still calling the shots for the party.